Measurement of Nitrogen Fixed by Pueraria Phaseloides by N-15 Dilution Technique - Abdul Rahman, Zaharah; Abdul Hamid, Sharifuddin; Mohammed Nordin, Razley; Abdul Kadir, Mohd Saidi (1986)
A field experiment was carried out to determine the amount of nitrogen fixed by Pueraria phaseloides which was grown as a cover in the interrow of two-year old oil palms (Elaeis guineensis) in Seafield Estate, Batu Tiga, Selangor. The grasses that were found growing together with the legume cover were Paspalum congugatum and Ottochloa nodosa. Plots of 1 m by 1 m were randomly selected within the inter rows of the palms to give various mixtures of grass and legume. These plots were cut at 5 cm above the ground, and applied with 2 g Nlm 2 as ammonium sulphate enriched with 10% atom excess N-15. The regrowth of the legume and grass were harvested after three months, and analysed for total N and N-15 enrichment of the tissues. The. results show that there were significant differences in total N fixed by Peurana mixed with different percentages of grass. At 0 - 40% legume composition, the total N fixed by Peurana was 9.20 kg lha/3 months and increased to 22.34 and 37.80 kgIhal3 months at 41 - 60% and 61 - 80% respectively. Total N fixed at 81 - 100% legume composition was 22. 73 kg lha/3 months. The maximum amount of N fixed by Peuraria was when the mixture contained about 80% legume standing.